A Bibliometric Analysis of Research Trends on Blockchain in Finance: Insights into Transparency, Security, and Collaboration Networks - Yohanna Thresia Nainggolan; Bella Lisa Permatasari; Muh. Irfandy Azis; Irawati HM; Ferica Christinawati Putri (Ilomata International Journal of Tax and Accounting, 2026)
Introduction: Blockchain technology has emerged as a transformative innovation in the financial sector by enhancing transparency, security, and operational efficiency. As academic interest in blockchain applications continues to grow, understanding the development, structure, and direction of research in this field has become increasingly important. Novelty: Although previous studies have examined blockchain broadly, limited research has specifically mapped the intellectual structure, thematic evolution, and collaboration patterns of blockchain research in finance, particularly regarding transparency and security. To address this gap, the present study provides a comprehensive bibliometric mapping of blockchain research in finance from the perspectives of transparency and security. Methods: This study applies a bibliometric analysis approach to 256 Scopus-indexed publications related to blockchain in finance. Data were analyzed using the Bibliometrix package in R to examine annual scientific production, keyword co-occurrence, thematic development, historiographic structure, and collaboration networks among authors, institutions, and countries. Results: The findings reveal a significant increase in blockchain-related publications, particularly after 2021, indicating growing scholarly attention. Major research themes include blockchain foundations, security and privacy, decentralized finance, regulation, and cross-sector applications. The analysis also demonstrates increasingly interconnected global collaboration networks led by several productive countries. Conclusion: Overall, the findings indicate that blockchain has become an increasingly prominent research domain within financial studies. This study contributes by providing a comprehensive mapping of research trends and offering insights for future studies and policy development related to transparency and security in digital financial systems.